2009
DOI: 10.1021/ef9009394
|View full text |Cite
|
Sign up to set email alerts
|

Base Catalysts Derived from Hydrocalumite for the Transesterification of Sunflower Oil

Abstract: This work investigates the use of a layered Ca-Al double hydroxide (hydrocalumite) as precursor, after its thermal activation, of base catalysts for the methanolysis of sunflower oil. Above 750 °C, hydrocalumite is transformed into a mixture of CaO and mayenite (Ca 12 Al 14 O 33 ). Another Ca-Al material obtained under similar experimental conditions was also studied, but using the Ca/Al molar ratio of the mayenite, 12:14. A sunflower oil conversion of 97% has been reached with a methanol/oil molar ratio of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…In the methanolysis of palm kernel oil over this catalyst the FAME yield of 98% was achieved within 2 h. Despite a loss of activity because of methanol leaching (110 ppm of Ca þMg), the FAME yield higher than 90% was maintained within seven repeated cycles. Also, hydrotalcite-like materials are good precursors for the preparation of heterogeneous transesterification catalysts [64,[110][111][112]. Metal oxides with a high surface area and with strong Lewis base sites are derived from these materials by thermal decomposition.…”
Section: Mixed Oxides Catalysts Containing Caomentioning
confidence: 99%
“…In the methanolysis of palm kernel oil over this catalyst the FAME yield of 98% was achieved within 2 h. Despite a loss of activity because of methanol leaching (110 ppm of Ca þMg), the FAME yield higher than 90% was maintained within seven repeated cycles. Also, hydrotalcite-like materials are good precursors for the preparation of heterogeneous transesterification catalysts [64,[110][111][112]. Metal oxides with a high surface area and with strong Lewis base sites are derived from these materials by thermal decomposition.…”
Section: Mixed Oxides Catalysts Containing Caomentioning
confidence: 99%
“…In recent years, these compounds have been applied successfully as hardening accelerator in concrete (Xu et al, 2009) and other distinct applications which include: aldol condensation (Cota et al, 2010), transesterification (Campos-Molina et al, 2010;Kuwahara et al, 2012;Sankaranarayanan et al, 2012), cycloaddition (Kuwahara and Yamashita, 2013), isomerization (López-Salinas et al, 1996), Meerwein-Ponndorf-Verley reaction (Aramendía et al, 2001;Mora et al, 2010), in situ polymerization of interleaved monomers (Vieille et al, 2004) and intercalation (Plank et al, 2008) reactions. Additionally, HC and HLC materials have been employed in environmental remediation for chloride, nitrate and carbonate (Phillips and Vandeperre, 2011), borate, sulfate, and arsenate (Reardon and Valle, 1997), chromate and phosphate (Qian et al, 2012), Cd 2+ , B, Cr, Mo, and Se (Hang and Reardon, 2003), Zn 2+ (Liu et al, 2011), perchlorate (Kim et al, 2011), dye (Pereira de Sá et al, 2013); (Zhang et al, 2012a) and organic pollutant (Zhang et al, 2012b) removal.…”
Section: Introductionmentioning
confidence: 99%
“…They are due to metal-oxygen bonds 9 . By examining the results of Vieille et al 6 , López-Salinas et al 7 and Campos-Molina et al 12 , it can be concluded that the transformation of hydrocalumite during the calcination occurs in three steps: in the first one (25-200°C), the physisorbed water is lost from the hydrocalumite structure. The second (200-400°C) and third steps (400-800°C) correspond to dehydroxylation and expulsion of anions.…”
Section: Evaluation Of Calcined Hydrocalumite-type Materials As Suppomentioning
confidence: 97%
“…The second (200-400°C) and third steps (400-800°C) correspond to dehydroxylation and expulsion of anions. An exact sequence has not been established, however, it was reported that the material still losses water from dehydroxilation at temperatures above 600°C 12 . This could explain water molecule bands of the material observed on HC 420 (Figure 1b).…”
Section: Evaluation Of Calcined Hydrocalumite-type Materials As Suppomentioning
confidence: 99%